Addressing the silence: A study on the underreporting of sexual violence among female garment workers in Bangladesh - Habiba Lilun Nahar (Global Labour University - Freunde und Förderer e.V., 2024)
Sexual violence against female garment workers in Bangladesh is a pervasive problem that often goes unreported due to various factors. This research aims to address the silence surrounding the underreporting of sexual violence among female garment workers in Bangladesh. The study has utilized a case study approach, incorporating semi-structured interviews with female garment workers who have experienced sexual violence and examining the systemic factors within the garment industry that perpetuate such violence. The research is grounded in the feminist political economy framework, which analyses the power dynamics, gender inequalities, and patriarchal norms that contribute to the underreporting of sexual violence. The findings of this study illuminate the extent of sexual violence within the Ready-made Garment (RMG) sector. Fear of retaliation and job instability, power imbalance, cultural norms and stigmatization, economic insecurity and institutional barriers are identified as the main factors of underreporting violence. Furthermore, the research delves into themes of women's empowerment and agency, shedding light on the current status of female empowerment within the RMG industry. Finally, the study concludes that addressing underreported violence and promoting empowerment require comprehensive actions. Vital steps include establishing clear reporting systems, conducting awareness campaigns, implementing training initiatives, and fostering collaboration among stakeholders. These efforts empower female workers, encourage reporting of incidents, and contribute to combating gender-based violence in the workplace.
Keywords: 330